Evaluation of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and mean platelet volume in patients with lichen planus (Annals of Medical Research, 2021)
None
Keywords: Lichen Planus; Mean Platelet Volüme; Neutrophil-To-Lymphocyte Ratio; Platelet-To- Lymphocyte Ratio.